2004
DOI: 10.1111/j.1540-8183.2004.09880.x
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Dosing of N‐Acetylcysteine Prevents Contrast‐Induced Nephropathy After Elective and Urgent Coronary Angiography and Intervention

Abstract: An abbreviated, higher dose regimen of NAC prevents the rise of serum creatinine 48 hours after cath/PCI, and may prevent CIN after cath/PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 31 publications
(39 reference statements)
1
31
0
2
Order By: Relevance
“…30 Our study simultaneously compared multiple 35 36 treatment strategies using Bayesian network meta-analysis method, and found that 37 38 39 patients using CM were most likely to benefit from high-dose statin. The results of the 40 41 42 current study were similar to findings from previous primary studies [31][32][33][34] and meta- 43 44 45 analyses, 6,[35][36][37] which suggested that short-term prophylaxis with high-dose statins led 46 47 to a significant reduction in the risk of CI-AKI. In contrast, the meta-analysis by 1 Pre-existing renal dysfunction is an independent predictor of CI-AKI.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…30 Our study simultaneously compared multiple 35 36 treatment strategies using Bayesian network meta-analysis method, and found that 37 38 39 patients using CM were most likely to benefit from high-dose statin. The results of the 40 41 42 current study were similar to findings from previous primary studies [31][32][33][34] and meta- 43 44 45 analyses, 6,[35][36][37] which suggested that short-term prophylaxis with high-dose statins led 46 47 to a significant reduction in the risk of CI-AKI. In contrast, the meta-analysis by 1 Pre-existing renal dysfunction is an independent predictor of CI-AKI.…”
supporting
confidence: 80%
“…Of the 11 previous meta-analyses 29 30 31 published on this subject, seven found a net benefit of NAC in CI-AKI prevention. 32 …”
Section: 6mentioning
confidence: 99%
“…By contrast, in trials showing no effect of N-acetylcysteine, patients had had less severe renal insufficiency and a uniform 24-hour hydration protocol had been used (Table 6). In patients undergoing emergency diagnostic procedures, in whom a full hydration protocol is not possible, an abbreviated hydration regimen plus oral 90 or intravenous 91 administration of N-acetylcysteine was successful in reducing the rate of contrast-medium nephropathy. The development of contrast-medium nephropathy seems to depend on the amount of contrast agent given and on the dose of N-acetylcysteine.…”
Section: Low-dose Dopaminementioning
confidence: 99%
“…Duhram et al 17 found a CIN incidence of 26% when 1200 mg of NAC was administered before the administration of the contrast agent, and 1200 mg of NAC was given during the third hour after the administration of the contrast agent. Ochoa et al 18 reported that the incidence of CIN was 8% with NAC administered at similar dosages. In all three studies, which included mild-and low-risk patients, short-term NAC prophylaxis was used.…”
Section: Prepared (Preparation For Angiography Inmentioning
confidence: 98%
“…NAC was initiated within 1 hour before contrast administration and was given as a follow-up dose for 4 to 24 hours after the initial treatment. 17,18 Merten et al 19 compared sodium bicarbonate hydration with sodium chloride (NaCl) hydration in preventing CIN in azotemic patients. Sodium bicarbonate was initiated at 1 hour precontrast, with a follow-up dose 6 hours postcontrast.…”
mentioning
confidence: 99%